REVIEW: POTENTIAL OF NANOEMULGEL FORMULATIONS FOR TOPICAL DRUG DELIVERY - Santi Hasanah; Jessie Sofia Pamudji (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Nanoemulgel is a combination of two different formulation systems, known as nanoemulsion preparation with gel matrix. In recent years, there has been an increase in the use of topical nanoemulgel preparations because they are easy to apply and can avoid damage to various drugs in the body. Although topical nanoemulgel preparations have some limitations, they are capable of delivering lipophilic drugs topically. The purpose of this review is to summarize the potential of nanoemulgel formulations for topical drug delivery against various physiological challenges and limitations of the formula. Through the publication search, as many as 124 articles were obtained based on the screening results of 29 articles that met the inclusion criteria and were used as a review. The analysis of data for this article was conducted through a narrative review. This preparation may improve the permeability of the drug into the skin by penetrating the stratum corneum through intercellular and intracellular pathways, depending on the components used: oil phase, surfactants, co-surfactants, and gelling agents. Surfactants are responsible for damaging the structure of the skin layer by lowering the surface tension, and gelling agents are responsible for increasing the viscosity and adhesiveness of the skin. Nanoemulgel formulations for topical drug delivery can be used to treat several diseases, such as inflammation, arthritis, wounds, fungal infections, bacterial infections, and psoriasis. The nanoemulgel formulation may provide promising potential in delivering lipophilic drugs topically in the future Keywords: Nanoemulgel, nanoemulsion, gel, topical drug delivery